The Influence of Entrepreneurship Education and Self-Efficacy on Students' Entrepreneurial Interests (Case Study of Universitas Kristen Satya Wacana Students) - Dwi Indah Mega Utami; Sri Sulandjari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine which variable, entrepreneurship education or self-efficacy, influences entrepreneurial interest more. It is hypothesized that the influence of entrepreneurship education on entrepreneurial interest is greater than the influence of self-efficacy. This hypothesis was tested using stepwise regression. The subjects of this study were 100 students of the entrepreneurship concentration of the Faculty of Economics and Business (FEB) UKSW. The results of the data analysis showed a rejection of the hypothesis because it was found that the influence of the self-efficacy variable on entrepreneurial interest was greater than the influence of entrepreneurship education. Changes in the self-efficacy variable explained 48.9% of the variance (adjusted R² = 0.489). Including the entrepreneurship education variable only added 1.8% to the explanation of the variance in entrepreneurial interest (adjusted R² increased to 0.507). These findings suggest that the entrepreneurship education curriculum, together with the teaching process, environment, and supporting facilities, must foster an entrepreneurial spirit to improve students' standards and enthusiasm for pursuing an entrepreneurial career.